1997
DOI: 10.1023/a:1018542313236
|View full text |Cite
|
Sign up to set email alerts
|

A study of cell behaviour on the surfaces of multifilament materials

Abstract: Since many fibres are very strong, they are considered to have useful potential for fibre reinforcement of orthopaedic and dental implant materials. Fibres exposed on the surface of composites may significantly influence the cellular response not only due to the chemistry but also due to the fibre size and shape. This study has concentrated on investigation of cellular responses to fibre-specific aspects of fibre-reinforced composites. Four multifilament materials with diameter less than 20 microm were used: K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…This may further change the surface of the substrate and enhance cell adhesion and spreading. 2 Figure 1 shows that the fibroblast cells appeared to be attached and extended their filopodia on the surface of CO 2 laser-treated PET with three pulses, whereas, during the same culturing period, the fibroblast cells on the unmodified PET were in an early stage of attachment and almost round. The difference between cell appearances is likely to be a function of surface chemistry and surface morphology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may further change the surface of the substrate and enhance cell adhesion and spreading. 2 Figure 1 shows that the fibroblast cells appeared to be attached and extended their filopodia on the surface of CO 2 laser-treated PET with three pulses, whereas, during the same culturing period, the fibroblast cells on the unmodified PET were in an early stage of attachment and almost round. The difference between cell appearances is likely to be a function of surface chemistry and surface morphology.…”
Section: Discussionmentioning
confidence: 99%
“…1 A large number of groups have studied the interaction of biomedical materials with cultured cells because cell compatible materials are thought to be very important in many biomedical applications. [2][3][4][5] The control of cell adhesion to synthetic polymers is also a key factor in tissue engineering, which rests on the ability to direct specific cell types to proliferate, migrate, and express physiological behaviors in order to support and stimulate cellular architecture and tissue reconstraction. [6][7][8] Numerous in vitro experiments have shown that the cell behavior is influenced by the physicochemical properties of polymer surfaces such as wettability, chemistry, charge, roughness and rigidity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dimensions of the building components of a scaffold are important factors in regulating cell activities. 16,17 Cell behavior is known to be regulated by the physical properties of an engineered scaffold, such as the architecture and topography. Previous studies have shown that cell proliferation is influenced by the architectural scale of the structure and that adhesion is affected by the topography of the material.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is important to investigate how surface chemistry and structural unit of hybrid/composite scaffold can influence the cell transplantation process towards generation of new tissue or organ (37)(38)(39).…”
Section: Introductionmentioning
confidence: 99%